A documentation of Old Jiddah’s Ottoman arbiṭah (Poster): Selected case studies - Abbas, Hidaya M. (Proceedings of the Seminar for Arabian Studies, 2019)
Old Jiddah has a variety of historic buildings that are spread in the city’s four neighbourhoods: al-Shām, al-Yaman, al-Mazlūm, and al-Baḥr. Its rich architectural heritage includes houses of different sizes, mosques, governmental buildings, souks, and educational and pious foundations. The arbiṭah are significant examples of pious foundations in the city. This paper traces the history of the arbiṭah in Old Jiddah through the illustration of specific examples. The architectural analysis of each ribāṭ is preceded by an introduction on the ribāṭ’s location, importance, and brief history. Principally used as shelters, the functions of the arbiṭah are also described. This study aims to contribute an understanding of a relatively unknown part of the city’s architectural heritage.